Tathwīru Wasīlah Ta‘Līmiyyah Raqamiyyah Tafā‘uliyyah “al-Miftāh al-‘Araby” li-Tahsīn Mahārat al-Qirā’ah - Adiebah, Meilina Husna; Alfan, Muhammad; Dariyadi, Moch. Wahib; Chopipah, Binti; Shavir, Ravida Chauria (Mantiqu Tayr: Journal of Arabic Language, 2026)
The limited availability of interactive and student-centered digital media has become one of the challenges in developing Arabic reading skills, particularly in silent reading (qirā’ah ṣāmitah). This study aims to develop an interactive digital learning medium called Miftahul Aroby to enhance students’ Arabic reading skills (maharah al-qirā’ah) and to examine its feasibility and effectiveness. This research employed a Research and Development (R&D) approach using the ADDIE model, which involved needs analysis, design, development, implementation, and evaluation. Data were collected through expert validation, student questionnaires, and pretest–posttest assessments. The results demonstrate that Miftahul Aroby is feasible for use, as confirmed through expert validation covering linguistic accuracy, content relevance, interface design, and pedagogical suitability. The effectiveness of the media implementation was statistically verified through a pretest–posttest design. The Shapiro–Wilk test showed that the pretest scores were not normally distributed (Sig = 0.000 < 0.05), while the posttest scores followed a normal distribution (Sig = 0.130 > 0.05). The homogeneity test indicated non-homogeneous variances (Sig = 0.005 < 0.05); therefore, the Mann–Whitney test was applied. The results revealed a significant difference between pretest and posttest scores (U = 162.000, Z = –3.014, p = 0.003 < 0.05). These findings confirm a significant improvement in students’ reading comprehension, particularly in vocabulary mastery, identification of main ideas, and understanding of explicit and implicit meanings, along with increased learning motivation during the implementation phase. In conclusion, Miftahul Aroby contributes positively to Arabic reading instruction by providing an engaging and systematic digital learning experience. This study offers a practical contribution to the development of interactive digital media in Arabic language learning and suggests future research to explore its implementation on a wider scale and in different educational contexts.